Radio Watykańskie wobec stosunków państwo–Kościół w PRL w latach 1957–1979 - Jakubowska, Natalia (Pamięć i Sprawiedliwość, 2017)
Vatican Radio (RW) is tasked with providing information about the activities of the Pope and the Holy See, as well as the situations of Churches worldwide. The Polish Section of the Vatican Radio (SPRW) implemented these tasks, and among the many topics and information presented on the RW waves it also commented on issues related to State-Church relations in Poland. The aim of the article is to look in more detail, among others, on whether and how the SPRW presented the PRL state-Church relations during the period of 1957–1979. While presenting this topic, in the 60s, the SPRW usually drew from the opinions of the western press and foreign press agencies, and in the 70s primarily from the communications of the Polish Episcopacy Conferences. The SPRW informed its listeners about the most important issues affecting State-Church relations - among others, about the lack of religious freedom in PRL, persecution of the clergy, lack of permission for sacral buildings, efforts made by the Church for allowing it freedom in its actions and respecting human rights and the rights of Polish citizens by the PRL government. The SPRW defended the Polish clergy. Additionally, for the Polish people, the SPRW was the main source of uncensored information about the situation of the Church; not only worldwide, but primarily in Poland. The SPRW aired a series of educational programmes to counteract the attempts of secularisation of the society by the Communist government. The election of Karol Wojtyła as Pope contributed to the growth of the role of the Church in Poland, and made the SPRW face new challenges. It had its unparalleled contribution in accompanying the Pope during his pilgrimages and providing Polish listeners with the latest information not presented in the state media.